Comparative analysis of prevalence and antimicrobial resistance pattern of Staphylococcus aureus isolated from hospital effluents wastewater and hospital adjacent communities in Dhaka city - Tanni, Tanzina Islam (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.